2022
DOI: 10.1111/jpim.12620
|View full text |Cite
|
Sign up to set email alerts
|

Related and unrelated product diversification and collaboration strategies: Comparison between the pharmaceutical and biopharmaceutical industries

Abstract: In pharmaceutical and biopharmaceutical industries, developing and commercializing products require great investments and intensive clinical trials. With regard to managing the risk and uncertainty of such product development, especially given the low success rates, product diversification and collaboration strategies can be instrumental for firms. Especially, the differences in product development complexity and market condition among industries require more case-specific implications due to the absence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 176 publications
0
6
0
Order By: Relevance
“…In the first two situations, firms rely on new business units to enhance or exploit the current resources and capabilities, thus relatedness between businesses is necessary. However, in the third scenario, venturing into an unrelated industry is viewed as a viable and important strategy to stabilize cash flow (Kim et al ., 2022; Ng, 2007). Using 1,480 firm-year observations of public manufacturing firms, Ljubownikow and Ang (2020) found that firms facing a high level of competitive intensity would benefit more from unrelated diversification than related diversification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the first two situations, firms rely on new business units to enhance or exploit the current resources and capabilities, thus relatedness between businesses is necessary. However, in the third scenario, venturing into an unrelated industry is viewed as a viable and important strategy to stabilize cash flow (Kim et al ., 2022; Ng, 2007). Using 1,480 firm-year observations of public manufacturing firms, Ljubownikow and Ang (2020) found that firms facing a high level of competitive intensity would benefit more from unrelated diversification than related diversification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A indústria farmacêutica é considerada como uma das industrias mais complexas e dinâmicas da atualidade, caracterizadas pela alta intensidade em pesquisas e desenvolvimento e tecnologia de ponta (Banerjee;Siebert, 2017;Cardinal, 2001;Kim et al, 2022). Atuam em um segmento de pressão constante, os desafios sociais, tecnológicos e regulatórios exigem que as empresas biológicas respondam rapidamente a um ambiente em rápida mudança (Betz et al, 2014).…”
Section: Introductionunclassified
“…The advent of new technologies caused by the fourth industrial revolution makes the open innovation of companies more active and makes them perform more simultaneous open innovation than before (Phillips, 2021;Yun et al, 2019Yun et al, , 2021. As the open innovation process becomes more complex, actors have acquired various innovation capabilities Kim et al, 2020Kim et al, , 2022Shin et al, 2018). For example, universities have traditionally played a role in R&D and education, but since the 2000s, as a corporate university, they have performed various roles such as business operation support, marketing support and equipment support (Gassmann & Becker, 2006;Krishna, 2019;Schiuma & Carlucci, 2018;Yoshioka-Kobayashi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies focus on the R&D aspect in studying collaboration with universities and research institutes (Bogers & Lhuillery, 2011). Furthermore, in real world, firms do not use collaborative partners as fixed roles of partner types, but they perform various collaborative activities with partners according to their strategy (Kim et al, 2015, 2016). In other words, the roles of actors are diversified and firms are using them strategically.…”
Section: Introductionmentioning
confidence: 99%